Implementation of Digital Literacy in Elementary Schools - Masyhura, Nufaisah; Ramadan, Zaka Hadikusuma (International Journal of Elementary Education, 2021)
Digital literacy is one form of development in the 4.0 revolution era where we can access various desired information quickly. Of course, the digital literacy school environment impacts the learning process significantly. This study aims to analyze how the implementation of digital literacy in elementary schools. This type of research is qualitative with a research design in 4 stages: first, research focus. Second, research implementation (Observation, Interview). Third, data analysis. Fourth, the study results, the research subjects were 1 principal, 6 teachers and 6 students. Data collection techniques and research instruments include observation sheets and interview guidelines—data analysis using an interactive analysis model from Miles and Huberman. The study results show that the application of digital literacy in elementary schools is still not optimal. It is proven when conducting interviews and observations that the learning process is still teacher-centred and generally uses what app group digital literacy media is. In addition, the breakthrough about digital literacy in the school environment is still lacking, so that the implementation of digital literacy is only limited to understanding. Barriers experienced include students having difficulty understanding the material and limited internet quota. Therefore, to maximize the implementation of digital literacy in elementary schools, programs such as conducting training, manuals and digital literacy infrastructure are needed.